The Association between Long Noncoding RNA over Expression and Poor Prognosis of Liver Cancer: A Meta-Analysis. (24th November 2021) - Wang, Leiqing; Sheng, Junzhi; Zhang, Haojie; Xie, Baoyuan; Xiang, Linbiao; Liu, Dong; Zhang, Xinyuan; Zhang, Peihao; Liu, Jinjin
Abstract : Background . Long noncoding RNA (lncRNA) is considered to be a mediator of carcinogenesis, which may be associated with liver cancer survival. However, the relationship remains inconclusive. Meta-analysis was conducted to analytically review the association between the lncRNA expression level and clinicopathological characteristics and prognostic value of hepatic carcinoma. Materials and Methods . Four databases including Embase, PubMed, Web of Science, and the Cochrane Library were searched to collect studies about the relation between lncRNA overexpression and prognosis of liver cancer, dating from the earliest records of these databases to March 2021. Two researchers independently screened the data and literature to perform a stringent evaluation of the quality of material involved in the study. Meta-analysis was performed by Stata 16.0 software on 42 case-control studies with 6293 samples. Results . The outcomes of meta-analysis are presented as follows: lncRNA overexpression patients had later TNM stage (OR = 0.36, 95% CI (0.31, 0.41), P  < 0.001), lower histological grade (OR = 0.56, 95%CI (0.49, 0.65), P  < 0.001), more vascular invasion (OR = 2.02, 95% CI (1.74, 2.35), P  < 0.001), bigger tumor size (OR = 2.28, 95% CI (2.00, 2.60), P  < 0.001), more severe liver cirrhosis (OR = 1.39, 95% CI(0.1.16, 1.66), P  < 0.001), more likely to metastasize (OR = 1.80, 95%CI(1.49, 2.18), P  < 0.001), and more tumor numbers (OR = 0.72, 95% CI (0.62, 0.84), P  < 0.05). lncRNA over expression patients had shorter OS (HR = 2.32, 95 CI% (2.08, 2.59), P  < 0.01, RFS (HR = 2.19, 95 CI% (1.72, 2.78), P  < 0.01), and DFS (HR = 2.01, 95 CI% (1.57, 2.57), P  < 0.01). Conclusions . Overexposure of lncRNA is a poor prognostic feature for patients with hepatic carcinoma. The scope of our study was limited because of a lack of relevant research and the poor representativeness and varying quality of the studies involved in the current meta-analysis. Our conclusion still requires higher studies for further validation. This trial is clinically registered with CRD4201920620 .